2020
DOI: 10.3390/rs12111862
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Index for Burned Area Mapping: Integration of Multiple Spectral Indices Using Sentinel-2 Satellite Images

Abstract: Identifying fire-affected areas is of key importance to support post-fire management strategies and account for the environmental impact of fires. The availability of high spatial and temporal resolution optical satellite data enables the development of procedures for detailed and prompt post-fire mapping. This study proposes a novel approach for integrating multiple spectral indices to generate more accurate burned area maps by exploiting Sentinel-2 images. This approach aims to develop a procedure to combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 58 publications
(78 reference statements)
1
10
0
Order By: Relevance
“…In fact, validation clearly showed that RG provides the highest accuracy by reducing commission errors. Although a full comparison with published values is difficult due to the differences in input data and algorithms, our results are more than satisfactory and comparable to published reference values for accuracy metrics of burned area maps [64][65][66].…”
Section: Discussionsupporting
confidence: 76%
“…In fact, validation clearly showed that RG provides the highest accuracy by reducing commission errors. Although a full comparison with published values is difficult due to the differences in input data and algorithms, our results are more than satisfactory and comparable to published reference values for accuracy metrics of burned area maps [64][65][66].…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, a land cover mask was applied to minimize the negative effect, and it was worth considering the accuracy of the land cover mask as it could directly affect our detection result. In addition, the combination of multiple spectral indices can also be an alternative to cope with the confusion between burned and unburned areas [33,51]. Moreover, some isolated false detections appeared as salt-and-pepper noises, and a spatial filter with a moving window proved to be useful for reducing the noises and refining the results by following the majority vote rule [52].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the literature, the main remote sensing techniques for BA mapping include supervised and unsupervised classification methods, spectral indices, spectral mixture analysis, logistic regression modeling, principal component analysis, and recently, machine learning [7,13,15,[17][18][19][20]. The datasets used in these methods are generally bitemporal images or single post-fire images.…”
Section: Introductionmentioning
confidence: 99%